Mental health and wellbeing in the legal profession - Jones, Emma (Law teacher) (Bristol : Bristol University Press, 2020)
Legal professionals are thought to have higher levels of mental health issues and lower levels of wellbeing than the general population. Drawing on qualitative data from new research with legal practitioners, this in-depth study of mental health and wellbeing in the UK and Republic of Ireland's legal sector is a timely contribution to the urgent international debate on these issues. The authors present a comprehensive discussion of the cultural, structural and other causes of legal professionals' compromised wellbeing. They explore the everyday demands and difficulties of the legal working environment and consider the impacts on individuals, the legal profession and wider society. Making comparisons with systems overseas, this is an invaluable resource that provides evidence-based suggestions for swift and effective organisational and policy-related interventions in the legal sector.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Lawyers -- Mental health -- Great Britain; Lawyers -- Mental health -- Ireland